Parsing gaps: Evidence from French. - Bourdages, Johanne S. (University of Ottawa (Canada), 1990)
This dissertation investigates the parsing of filler-gap dependencies in French, more specifically those found in the restrictive relative construction. The primary goal of this research is to examine a question raised by Stowe (1984; 1986) concerning whether the parser has access to islandhood knowledge. Stowe's (1984;1986) results are compatible with the view that this type of grammatical information is readily accessible for the parser's initial analysis. However, her results are ambiguous since in her study, islandhood was confounded with subject position, where she failed to find gap-location effect. This study will examine the CNP-constraint in object position. A second goal is to examine whether the parsing mechanism postulates a gap in any potential position or only when the position is also a potential end of the sentence. Most of the experiments in the field use sentences where false gaps are located in a position which can correspond to a potential end of a sentence. Thus, the "surprise" effect attributed to false gap filling could also be attributed to the parsing mechanism finding that it did not reach the end of the sentence as expected. This dissertation provides evidence compatible with the view that island constraints, in this case the Complex NP constraint, are readily available to the parser; however, it also provides indications that the potential end of the sentence effect is a factor which has to be considered in identifying a gap location.
Keywords: Language, Linguistics.